2022
DOI: 10.3389/fmedt.2022.934015
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics pharmacokinetic model for targeted nanoparticles

Abstract: Nanoparticles (NP) are being increasingly explored as vehicles for targeted drug delivery because they can overcome free therapeutic limitations by drug encapsulation, thereby increasing solubility and transport across cell membranes. However, a translational gap exists from animal to human studies resulting in only several NP having FDA approval. Because of this, researchers have begun to turn toward physiologically based pharmacokinetic (PBPK) models to guide in vivo NP experimentation. However, typical PBPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Both studies were able to demonstrate that multicompartment models and systems of differential equations were able to recapitulate in vivo data. More so in their studies, they highlighted the predictive power of these models by predicting how nanoparticle formulation parameters could alter transport efficiency. , A key part of these studies is linking theoretical kinetic data with in vivo data. Neubauer et al were able to use MRI as a method to validate three-compartment models in pharmacological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies were able to demonstrate that multicompartment models and systems of differential equations were able to recapitulate in vivo data. More so in their studies, they highlighted the predictive power of these models by predicting how nanoparticle formulation parameters could alter transport efficiency. , A key part of these studies is linking theoretical kinetic data with in vivo data. Neubauer et al were able to use MRI as a method to validate three-compartment models in pharmacological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these solvers are connected with external codes, which are compiled either from FORTRAN or C. Following a detailed study of different problem classes with respective ODE solvers, Andersson et al ( 2015 ) proposed to increase the variety of original codes and make them available through the framework provided. Furthermore, a dedicated study on multiphysics pharmacokinetic models demonstrated the need for ODE solvers in compartmental modelling (Glass et al 2022 ). The motivation for this recent study was that physiologically-based pharmacokinetic (PBPK) models use an empirically derived framework that cannot be universally applied to varying nanoparticle constructs and experimental settings.…”
Section: Ode Solvers and Solving Methodsmentioning
confidence: 99%
“…According to Glass et al ( 2022 ), two versions of physics-based compartmental models were developed, for which the stiff ODE solving methods used were from MATLAB and Julia (Rackauckas 2017 , Bezanson et al 2017 ) and validated against experimental data. Julia was developed as an alternative to Python and MATLAB.…”
Section: Ode Solvers and Solving Methodsmentioning
confidence: 99%
See 2 more Smart Citations